The Mediating Role of Organizational Citizenship Behavior (OCB) on Employee Performance: Locus of Control and Self-Efficacy - Amirul Syah; Safrida Safrida (Qubahan Academic Journal)
This research aimed to determine and analyze the influence of locus of control, self-efficacy, and Organizational Citizenship Behavior (OCB) on employee performance, on OCB, and through OCB and to find out and analyze the influence of self-efficacy, on employee performance through OCB at a Hospital Company in Medan. The population in this study was 180 employees of the Hospital Company in Medan, with a research sample of 64 employees who were measured using the Slovin formula. The data collection techniques used in this research were questionnaires and interviews. Meanwhile, the analysis technique used SmartPLS (Partial Least Square), starting from model measurement (outer model), model structure (inner model), and hypothesis testing. The research results showed that locus of control, self-efficacy, and OCB influence employee performance, locus of control and self-efficacy influence OCB, locus of control influences employee performance through OCB and self-efficacy influences employee performance through OCB at a Hospital Company in Medan.